Current uses and outcomes of lumen-apposing metal stents - Mussetto, Alessandro (Ann Gastroenterol, 2018)
The lumen-apposing metal stent (LAMS) is one of the revolutionary devices recently developed for gastrointestinal endoscopy. This device has a saddle-shaped design and large lumen. It was originally designed for drainage of transmural pancreatic fluid collection and in the last few years it has been used extensively for that indication. More recently, other in- and off-label indications have been proposed. Several types of LAMS are available, with or without an electrocautery-enhanced delivery system. In the current review we discuss the state of the art with regard to LAMS and their indications, usage, and outcomes.